PRINCIPLES OF DEVELOPMENT OF ENTREPRENEURIAL COMPETENCIES IN STUDENTS BY VITAGEN EXPERIENCE - Pirniyazova Malika Ken`esbaevna (Western European Studies, 2024)
Competency in the article approaches based on of education a series aspects seeing passed. In particular professional, practical competence types and their development stages opinion about held. Particular attention is paid to the development of competencies that determine the basis of entrepreneurship in a person
Keywords: competence; assessment; information